1998
DOI: 10.1002/(sici)1099-1387(199805)4:3<211::aid-psc138>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from bovine brain: structure and biological role

Abstract: Fractionation of bovine brain extracts followed by automatic Edman sequencing of individual components resulted in identification of 107 endogenous peptides formed from functional proteins (haemoglobin, myelin basic protein, cytochrome c oxidase, etc) or unknown precursors. Several of the newly identified brain peptides demonstrate different types of biological activity; some of the substances show considerable overlap with the known biologically active peptides. It is suggested that these peptides should part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…Analogously, the content of neokyotorphin in rat lung tissue is 10–15‐fold higher than in the rat brain [21]. Brain extracts also contain fragments of neurospecific proteins [15, 16], the spleen extract is enriched with fragments of β‐actin [26].…”
Section: Tissue‐specific Peptide Pool – the Results Of Endogenous Protmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously, the content of neokyotorphin in rat lung tissue is 10–15‐fold higher than in the rat brain [21]. Brain extracts also contain fragments of neurospecific proteins [15, 16], the spleen extract is enriched with fragments of β‐actin [26].…”
Section: Tissue‐specific Peptide Pool – the Results Of Endogenous Protmentioning
confidence: 99%
“…In particular, a novel family corresponding to the (84–95) segment of the hemoglobin α‐chain was discovered in the supernatant, as well as a novel pattern of formation of the peptides corresponding to β‐chain segment (12–31). The related family found in bovine brain extract [15]is formed upon cleavage of β‐globin (14–28) at the Asp 20 –Glu 21 site giving rise to two groups of both N‐ and C‐terminally shortened peptides. In contrast, in the erythrocytes the tertiary splitting takes place at Val 11 –Thr 12 (instead of Leu 13 –Trp 14 ) and the resultant fragments are in turn cleaved at two sites (Val 17 –Asn 18 and Asp 20 –Glu 21 ) forming two families of overlapping peptides.…”
Section: Formation Of the Components Of Tissue‐specific Peptide Poolsmentioning
confidence: 99%
“…The elution profiles from individual brain specimens were highly reproducible, proving the stability of the peptide composition of brain tissue, analogous to the peptide panels of bovine brain [1,2] and cerebellum [7,18,19] extracts. The typical chromatograms of the fractions I -IV are given in Figures 2 -5.…”
Section: Resultsmentioning
confidence: 76%
“…Structural analysis of the low molecular weight components of bovine brain [1,2] and red bone marrow [3] extracts, lysate of human erythrocytes [4,5], extract of rat brain [6] and human cerebellum [7] has demonstrated that these sources mainly contain the fragments of functional proteins, in particular, hemoglobin. The number of components corresponding to chromatographic peaks, distinguishable in the chromatograms varies from 15 -25 to 800-1500, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation